Performance of Equity Mutual Funds considering ESG investments, Financial Constraints, and the COVID-19 Pandemic - Thayse Machado Guimarães; Rodrigo Fernandes Malaquias (BBR: Brazilian Business Review)
In this paper, we analyzed the risk-adjusted performance of funds related to Environmental, Social and Governance (ESG-related funds), considering periods of financial constraints and the COVID-19 Pandemic. The database is comprised of 3,840 equity mutual funds in the period from January/2006 to December/2020. Each year, considering daily returns, we employed the Returns-Based Style Analysis to classify each fund as an ESG-related fund or a conventional fund; all funds in the category “Equities - Sustainability / Governance” were also considered as ESG-related mutual funds. Using daily data, for each year, the performance was estimated based on the four-factors model. The main results indicate that, on average, ESG-related funds presented higher risk-adjusted returns during periods of financial constraints. These results suggest that, during market downturns, investors tend to obtain better risk-adjusted returns for investing in green funds. A similar result was observed in relation to the COVID-19 period, suggesting that, based on the methods and procedures used, ESG-related funds achieved a better performance when compared to “conventional” funds during the Pandemic.